2022
DOI: 10.3390/biomedicines10061376
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Potential Rationale of Immunotherapy in Peritoneal Metastasis of Advanced Gastric Cancer

Abstract: Peritoneal metastasis (PM) is one of the most frequent metastasis patterns of gastric cancer (GC), and the prognosis of patients with PM is very dismal. According to Paget’s theory, disseminated free cancer cells are seeded and survive in the abdominal cavity, adhere to the peritoneum, invade the subperitoneal tissue, and proliferate through angiogenesis. In these sequential processes, several key molecules are involved. From a therapeutic point of view, immunotherapy with chemotherapy combination has become t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Although the level of medical technology continues to improve, the diagnosis and treatment of gastric cancer are still not optimistic, and the 5-year overall survival rate is less than 30% [ 2 ]. Cancer cell metastasis is the main reason affecting the curative effect of gastric cancer [ 22 , 23 ]. Therefore, actively exploring the mechanism of gastric cancer metastasis, selecting appropriate diagnostic markers, and discovering new therapeutic targets are crucial for improving the survival rate of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the level of medical technology continues to improve, the diagnosis and treatment of gastric cancer are still not optimistic, and the 5-year overall survival rate is less than 30% [ 2 ]. Cancer cell metastasis is the main reason affecting the curative effect of gastric cancer [ 22 , 23 ]. Therefore, actively exploring the mechanism of gastric cancer metastasis, selecting appropriate diagnostic markers, and discovering new therapeutic targets are crucial for improving the survival rate of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Defining an approach to address these targets is challenging. In particular, systemic drug administration has the disadvantage of having limited access to the abdominal compartment and the possibility of producing systemic toxicity [ 17 ]. Therefore, the direct administration of immunotherapies into the peritoneal cavity represents an interesting strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence demonstrated that TGF β1 pathway plays an important part in the reciprocal communication of GC cells and mesothelial cells [ 45 ]. TGF β1 could lead to receptors Smad 2/3 phosphorylation, and then the phosphorylated Smad2/3 are translocated into nucleus where they will bind to Smad4 to form a heteromeric complex, and the latter could serve as transcription factor to regulate gene expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%